Fixed-prosthodontics in Nigerian private practice settings - Ikusika OF; Idon PI; Alalade O; Sotunde AO; Akinpelu MA; Igweagu CE (Ibom Medical Journal, 2022)
Context: Private practice dentistry is predominant in Nigeria. Audits of fixed-prosthodontic practice in these settings are rare and will highlight capacity and guide training. This study aimed to assess the scope and quality of fixed-prosthodontic practice in such settings in Nigeria.